Technological transition from IPv4 to IPv6 at SNR: A success case - Salinas Gonzalez, Andersson; Escobar Díaz, Andrés; Vacca González, Harold (Ingeniería Solidaria, 2021)
Introduction:The article is the product of the research “Technological transition IPv4 - IPv6 protocol" developed at the Francisco José de Caldas District University in 2020.Problem: There is no detailed plan for the transition to IPv6 for the SNR that solves the support and connectivity problems of new devices to compete more efficiently in the telecommunications market for access to officials and the population.Objective: To Generate a transition process plan that includes a detailed description of the phases and includes the key activities for said transition.Methodology: This article, therefore, describes the research and implementation project that led to determine activities, phases and products corresponding to the technological transition from IPv4 to IPv6 in the SNR.Results: The scope is visualized, as well as the documentary assurance through actions and recommendations of the change.Conclusion: It is evident that, after complying with a proposed evaluation methodology, the experience can be characterized as a case of success, since it facilitated the pertinent decision making within the process of adopting the new protocol.Originality: Through this research, the three transition phases suggested by the Ministry of Information Technologies and Communications (MinTIC) are contemplated.Limitations: The technological transition from the IPv4 to IPv6 protocol is limited to the fact that the process is not immediate but transitory, so it must be supported by transition mechanisms that allow the coexistence of both protocols.